Hydraulic traits and photosynthesis are coordinated with trunk sapwood capacitance in tropical tree species - Wei, Yang; Chen, Ya-Jun; Siddiq, Zafar; Zhang, Jiao-Lin; Zhang, Shu-Bin; Jansen, Steven; Cao, Kun-Fang (Tree physiology, 2023)
Abstract Water stored in trunk sapwood is vital for the canopy to maintain its physiological function under high transpiration demands. Little is known regarding the anatomical properties that contribute to the hydraulic capacitance of tree trunks and whether trunk capacitance is correlated with the hydraulic and gas exchange traits of canopy branches. We examined sapwood capacitance, xylem anatomical characteristics of tree trunks, embolism resistance, the minimal xylem water potential of canopy branches, leaf photosynthesis and stomatal conductance in 22 species from a tropical seasonal rainforest and savanna. The results showed that the mean trunk sapwood capacitance did not differ between the two biomes. Capacitance was closely related to the fiber lumen fraction and fiber wall reinforcement and not to the axial and ray parenchyma fractions. Additionally, it was positively correlated with the theoretical hydraulic conductivity of a trunk and the specific hydraulic conductivity of branches, and showed a trade-off with branch embolism resistance. Species with a high trunk sapwood capacitance maintained less negative canopy water potentials in the dry season, but higher leaf photosynthetic rates and stomatal conductance in the wet season. This study provides a functional link among trunk sapwood capacitance, xylem anatomy, canopy hydraulics and photosynthesis in tropical trees.